1989
DOI: 10.1143/jjap.28.l75
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ca2PbO4 Addition on Superconductivity in a Bi-Sr-Cu-O System

Abstract: We examined the effect of Ca2PbO4 addition on superconductivity in a Bi-Sr-Cu-O system. We determined that Ca2PbO4 is formed in Bi-Pb-Sr-Ca-Cu-O at temperatures lower than 750°C on the basis of powder X-ray diffraction and micro-Raman scattering. A high-T c phase was synthesized by adding Ca2PbO4 to the Bi-Sr-Cu-O system which has a single CuO layer. It seems that the synthesis process of the high-T c phase is based on a reaction between the low-T c structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1

Year Published

1990
1990
2002
2002

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(16 citation statements)
references
References 5 publications
1
14
1
Order By: Relevance
“…An alternative route for the formation of Bi2223 would be to start the reactions from calcined powders composed of Bi2212 and secondary phases such as Ca 2 PbO 4 , CaCuO 3 or CuO [5][6][7][8][9]. This would allow the plate-like grains to reorient more easily because of the large amount of liquid phase.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative route for the formation of Bi2223 would be to start the reactions from calcined powders composed of Bi2212 and secondary phases such as Ca 2 PbO 4 , CaCuO 3 or CuO [5][6][7][8][9]. This would allow the plate-like grains to reorient more easily because of the large amount of liquid phase.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of the 2223 phase is believed to proceed by a reaction between Bi 2 Sr 2 Ca 1 Cu 2 O y (hereafter referred to as "2212"), alkaline earth cuprate phases, and a liquid phase. [8][9][10][11][12][13][14][15][16][17] One of the most effective ways to make a nearly phase-pure 2223 microstructure is to blend Pbdoped 2212 powder with a mixture of Ca 2 CuO 3 and CuO. 15,16 This so-called "two-powder" mixture reacts quickly to the 2223 phase, leaving only small (Ca,Sr) 2 CuO 3 particles as the principal residual second phase.…”
Section: Introduction 1234567891011121314151617mentioning
confidence: 99%
“…The difficulty in preparing the high-T~ phase revealed that an understanding of the formation of high-T~ phase is prerequisite for the fabrication of superconductors containing pure high-To phase with high quality. The formation mechanism of the high-To phase was extensively discussed by many authors [6][7][8][9][10][11]. Even 0957 4522 ~; 1996 Chapman & Hall though different approaches were made so far, many points concerning the formation mechanism of the high-To phase are still obscure.…”
Section: Introductionmentioning
confidence: 99%